Sandovals celebrate 50th (Raton Range Raton, New Mexico, 1984)
Newspaper Article on the 50th Anniversary of Mr. & Mrs. Leandro Sandoval.
Master list item #: 22
File location is in the Raton File Cabinet
Keywords: Sandoval, Leandro; Sandoval, (Mrs.); Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico